Operation Airway: The First Sustainable, Multidisciplinary, Pediatric Airway Surgical Mission. (October 2014) - Rogers, Derek J.; Collins, Corey; Carroll, Ryan; Yager, Phoebe; Cummings, Brian; Raol, Nikhila; Setlur, Jennifer; Maturo, Stephen; Tremblay, Sarah; Quinones, Ernesto; Noviski, Natan; Hartnick, Christopher J.
Objective: This study aimed to describe the development and implementation of the first sustainable, multidisciplinary, pediatric airway surgical mission in an underserved country. Methods: This prospective, qualitative study was conducted for the first 4 Operation Airway missions in Quito, Ecuador. The major goals of the missions were to assist children with aerodigestive abnormalities, create a sustainable program where the local team could independently provide for their own patient population, develop an educational curriculum and training program for the local team, and cultivate a collaborative approach to provide successful multidisciplinary care. Results: Twenty patients ages 4 months to 21 years were included. Twenty-three bronchoscopies, 5 salivary procedures, 2 tracheostomies, 1 T-tube placement, 1 tracheocutaneous fistula closure, 2 open granuloma excisions, and 6 laryngotracheal reconstructions (LTRs) were performed. All LTR patients were decannulated. A new type of LTR (1.5 stage) was developed to meet special mission circumstances. Two videofluoroscopic swallow studies and 40 bedside swallow evaluations were performed. One local pediatric otolaryngologist, 1 pediatric surgeon, 3 anesthesiologists, 7 intensivists, 16 nurses, and 2 speech-language pathologists have received training. More than 25 hours of lectures were given, and a website was created collaboratively for educational and informational dissemination (http://www.masseyeandear.org/specialties/pediatrics/pediatric-ent/airway/OperationAirway/ ). Conclusion: We demonstrated the successful creation of the first mission stemming from a teaching institution with the goal of developing a sustainable, autonomous surgical airway program.